Service design from staffing to outsourcing - Jerónimo, C. H.; Pereira, L.; Lopes da Costa, R.; Dias, Á. (International Journal of Service Science, Management, Engineering, and Technology, 2022)
The term outsourcing has become a conventional means of describing anything associated with the transaction of services that enables client organisations to blur core activities and thereby reduce their internal workforce and costs. The main objective of this study is confirming a gap in detailed and spe-cific reviews of formats and economic transactions through non-standard forms of employment, namely in a service design model from Staffing to Outsourcing. The literature review was performed using text mining and topic modelling techniques to group relevant topics and decreases the likelihood of human bias, while bringing robustness to the analysis. The results are reflected in a conceptual state of the art diagram that will serve as a basis to new discussions.